Reactivation and Lytic Replication of Kaposi’s Sarcoma-Associated Herpesvirus: An Update - Aneja, Kawalpreet K.; Yuan, Yan (Frontiers in Microbiology, 2017)
The life cycle of Kaposi's sarcoma-associated herpesvirus (KSHV) consists of two phases, latent and lytic. The virus establishes latency as a strategy for avoiding host immune surveillance and fusing symbiotically with the host for lifetime persistent infection. However, latency can be disrupted and KSHV is reactivated for entry into the lytic replication. Viral lytic replication is crucial for efficient dissemination from its long-term reservoir to the sites of disease and for the spread of the virus to new hosts. The balance of these two phases in the KSHV life cycle is important for both the virus and the host and control of the switch between these two phases is extremely complex. Various environmental factors such as oxidative stress, hypoxia, and certain chemicals have been shown to switch KSHV from latency to lytic reactivation. Immunosuppression, unbalanced inflammatory cytokines and other viral coinfections also lead to the reactivation of KSHV. This review article summarizes the current understanding of the initiation and regulation of KSHV reactivation and the mechanisms underlying the process of viral lytic replication. In particular, the central role of an immediate-early gene product RTA in KSHV reactivation has been extensively investigated. These studies revealed multiple layers of regulation in activation of RTA as well as the multifunctional roles of RTA in the lytic replication cascade. Epigenetic regulation is known as a critical layer of control for the switch of KSHV between latency and lytic replication. The viral noncoding RNA, PAN, was demonstrated to play a central role in the epigenetic regulation by serving as a guide RNA that brought chromatin remodeling enzymes to the promoters of RTA and other lytic genes. In addition, a novel dimension of regulation by microPeptides emerged and has been shown to regulate RTA expression at the protein level. Overall, extensive investigation of KSHV reactivation and lytic replication has revealed a sophisticated regulation network that controls the important events in KSHV life cycle.